Influence of mindfulness and coping flexibility in the early phases of burnout development in intensive care unit healthcare workers during the COVID-19 pandemic - Damien Claverie; Anaïs Duffaud; Sonia Pellissier; Sandrine Jacob; Cécile Vigier; Marc Danguy des Déserts; Pierre Pasquier; Jacques Escarment; Frédéric Canini; Marion Trousselard (PLoS ONE, 2025)
Background Caregivers in intensive care units are exposed to high levels of stress, which were exacerbated during the COVID-19 pandemic, increasing the incidence of stress-related disorders, including burnout. Methods We evaluated the influence of mindfulness and coping flexibility in the early days of burnout development in a prospective study of 50 military caregivers working in a mobile resuscitation unit during the COVID-19 pandemic. We visited the participants at the end of deployment (day 0; D0) and three weeks later (D21). On D0, the participants completed questionnaires assessing mindfulness (Freiburg Mindfulness Inventory; FMI), coping flexibility (Flexcop), and burnout (Burnout Measure, Short Version; BMS). Subjective sleep symptoms were also assessed to evaluate their relationship with burnout. The BMS was repeated on D21. Results Four short-term burnout evolutions were observed: (i) “healthy” on D0 and D21; (ii) “exhausted,” healthy on D0 and burnout on D21; (iii) “resilient,” burnout on D0 and healthy on D21; and (iv) “burnout” on D0 and D21. Compared with healthy participants on D0, only resilient participants had lower FMI (η2 = 0.22; p = 0.032). Exhausted participants had more difficulty waking, and burnout participants had higher daytime fatigue than healthy participants. FMI scores on D0 negatively correlated with BMS scores on D21 (r = ‒0.40 r2 = 0.16 p = 0.009) for the entire population, and also after excluding burnout status at D0 (r = ‒0.41 r2 = 0.17 p = 0.02). Flexcop scores on D0 did not correlate with BMS scores on D21. Conclusions This study underlines the importance of mindfulness in the early days of burnout onset, and suggests considering its reinforcement for prevention of burnout and its measurement as a potential biomarker of burnout risk.